Effect of Educaplay Media on Grade VIII Al-Qur’an Hadith Learning Outcomes at MTSN 4 Ngawi - Faprilisya Heldhika Fani; Dina Rahayu Meylasari (ALSYS, 2026)
The use of innovative instructional media is one of the efforts to improve student learning outcomes, particularly in the Al-Qur’an Hadis subject. However, the learning outcomes of eighth-grade students at MTsN 4 Ngawi remain low due to the use of conventional instructional media that are less engaging and do not foster active student involvement, thereby necessitating more interactive learning media. One alternative form of digital instructional media that can be utilized is Educaplay. This study aimed to examine the effect of Educaplay-based instructional media on the learning outcomes of eighth-grade students in the Al-Qur’an Hadis subject at MTsN 4 Ngawi. A quantitative approach with an experimental method was employed, using a pre-test and post-test control group design. Data analysis included validity, reliability, normality, and homogeneity tests, as well as hypothesis testing using a t-test with the assistance of SPSS. The results showed that at the pre-test stage, the significance value (Sig. 2-tailed) was 0.413 > 0.05, indicating no significant difference between the two classes before the treatment. At the post-test stage, the significance value was 0.020 < 0.05, so H₀ was rejected and Hₐ was accepted, demonstrating that Educaplay-based instructional media had a significant effect on student learning outcomes. These findings affirm that the use of Educaplay as instructional media can improve learning outcomes and student participation, and therefore it is recommended that students focus more on understanding the material and that teachers adopt Educaplay as an alternative instructional medium, while future studies may broaden the scope of topics and subjects to test the consistency of this medium’s effectiveness.